First Description of the Composition and the Functional Capabilities of the Skin Microbial Community Accompanying Severe Scabies Infestation in Humans - Charlotte Bernigaud; Martha Zakrzewski; Sara Taylor; Pearl M. Swe; Anthony T. Papenfuss; Kadaba S. Sriprakash; Deborah Holt; Olivier Chosidow; Bart J. Currie; Katja Fischer (Microorganisms, 2021)
Epidemiological studies link Sarcoptes scabiei infection and impetigo. Scabies mites can promote Streptococcus pyogenes (Group A Streptococcus) and Staphylococcus aureus infections by breaching the skin barrier and excreting molecules that inhibit host innate immune responses. However, little is known about the composition and the function of the scabies-associated microbiota. Here, high-throughput whole-metagenome sequencing was used to explore the scabies-associated microbiome. Scabies mites including their immediate microenvironments were isolated from two patients with severe scabies in Northern Australia. Two ~45–50 million paired-end reads Illumina libraries were generated of which ~2 (5.1%) and 0.7 million (1.3%) microbial reads were filtered out by mapping to human (hg19) and mite draft genomes. Taxonomic profiling revealed a microbial community dominated by the phylum Firmicutes (A: 79% and B: 59%) and genera that comprise Streptococcus, Staphylococcus, Acinetobacter, and Corynebacterium. Assembly of the metagenome reads resulted in genome bins representing reference genomes of Acinetobacter baumannii, Streptococcus dysgalactiae (Group C/G), Proteus mirablis and Staphylococcus aureus. The contigs contained genes relevant to pathogenicity and antibiotics resistance. Confocal microscopy of a patient skin sample confirmed A. baumannii, Streptococci and S. aureus in scabies mite gut and faeces and the surrounding skin. The study provides fundamental evidence for the association of opportunistic pathogens with scabies infection.